Influence of temperature and time of exposure to temperature on the yield of the obtaining process of ethanolic and hydroethanolic extracts from Syzygium malaccense (L.) Merr. & L. M. Perry leaves - Sampaio, Daniela de Araújo; da Silva, Viviane Barrozo; Ricciotti, Antonio; Pequeno, Petrus Luiz de Luna; Montero, Ciro José Egoavil; Lima, Jorge Luis Nepomuceno de (International Journal for Innovation Education and Research, 2021)
The present study aimed to obtain alcoholic and hydroalcoholic (70% v/v) extract of Syzygium malaccense (L.) Merr. & L. M. Perry (red jambo fruit tree) leaves and investigated the influence of temperature and time of exposure to temperature on the extraction yield. It was applied a 2x2 factorial design, considering temperature and time of exposure as independent variables with two levels each: 30 or 60 °C for temperature and 60 or 120 minutes for time. For both ethanolic and hydroethanolic extraction, higher process yields were observed at higher temperature and time (24.26% and 19.00%, respectively), however, no significant difference was noticed when increasing the time of exposure to temperature.